1991
DOI: 10.1254/jjp.56.121
|View full text |Cite
|
Sign up to set email alerts
|

Footshock- and Psychological-Stress Prevent the Development of Tolerance to Spinal but Not Supraspinal Morpine.

Abstract: -The site of action involved in the suppression by exposure to footshock (FS) and psychological (PSY)-stress of the development of antinociceptive tolerance to morphine has been investigated. Daily treatment with 10 mg/kg, s.c.; 3,ag, i.t.; and 5,ug, i.c.v. of morphine, regardless of the administration route, resulted in the development of tolerance. Daily exposure to FS or PSY-stress suppressed the de velopment of tolerance to s.c. and i.t. administered morphine but not that to i.c.v. administered morphine. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a previous report, we demonstrated that the effect of morphine given daily i.t. was suppressed by the concomitant exposure to socio-psychological stress (30) or a subanalgesic dose of U-50,488H (27,28), both of which were antagonized by nor-binaltorphimine, implicating the k -receptor mechanism in the spine. The result shown here that SNL mice showed a persistent antinociceptive effect of U-50,488H when it was given i.t.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous report, we demonstrated that the effect of morphine given daily i.t. was suppressed by the concomitant exposure to socio-psychological stress (30) or a subanalgesic dose of U-50,488H (27,28), both of which were antagonized by nor-binaltorphimine, implicating the k -receptor mechanism in the spine. The result shown here that SNL mice showed a persistent antinociceptive effect of U-50,488H when it was given i.t.…”
Section: Discussionmentioning
confidence: 95%
“…Stressors such as pain (Melzack, 1990;Solan and Melzack, 1999;Javan et al, 2005), psychological stress (Takahashi et al, 1988(Takahashi et al, , 1992Tokuyama et al, 1989;Takahashi and Kaneto, 1991) and forced swim stress (Ghiafeh-Davoodi et al, 2005) prevent morphine tolerance.…”
Section: Introductionmentioning
confidence: 99%